Reference in Editing and Enlightenment: Case of Surah Al-Isra - KHETTOU , Zahra; TABTOUB , Sadjia (International Journal of Membrane Science and Technology, 2023)
Textual analysis is a fundamental topic in modern linguistics that focuses more on the text than on individual sentences. It necessitates a transition from studying the sentence as a major linguistic unit upon which language theories, schools, and trends are built, to studying the text. Reference is a semantic process governed by meaning and created by the speaker in the mind of the addressee through the use of words, sometimes ambiguous in their own meaning, such as pronouns that refer to objects or individuals, chains of sentences, or even entire texts outside or within the linguistic or non-linguistic context, whether preceding or following it. It serves various purposes, including linguistic economy by substituting for previously mentioned speech and connecting the elements of the text to achieve textual continuity and cohesion.